Development of Statistical Model to Evaluate the Effect of Meteorological Parameters on the Performance of PV-Cell/Module - ., Sanjay; Berwal, Anil K (Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2020)
The growing need for energy by the human society, climate change and depletion of conventional energy sources demands a renewable, safe, illimitable and low-price energy source. One of the best applicable means to break the accountable world’s activity crisis is to use the authority of the sun. Solar activity is clean, great and environment-amicable abeyant ability amid renewable activity options. Solar Photovoltaic (SPV) cells/ modules are composed of silicon or other semi-conductive materials. Semiconductor materials have negative temperature coefficient. The photovoltaic module power output/efficiency depends linearly on the operating temperature while operating temperature of photovoltaic module is depends on the meteorological parameters such as: wind speed, humidity, sky condition etc. In order to predict the energy production of photovoltaic (PV) modules, it’s far compulsory to presage the PV module temperature as a function of ambient temperature, wind speed, wind direction, total irradiance, and relative humidity. This paper presents a statistical model to evaluate the effect of meteorological parameters on the performance of PV cell/module and predict the modules efficiency & module temperature. How to cite this article: Sanjay, Berwal AK. Development of Statistical Model to Evaluate the Effect of Meteorological Parameters on the Performance of PV-Cell/ Module. J Adv Res Alt Energ Env Eco 2020; 7(1): 1-7. DOI: https://doi.org/10.24321/2455.3093.202001